Successful Extracorporeal Membrane Oxygenation (ECMO) Use without Systemic Anticoagulation for Acute Respiratory Distress Syndrome in a Patient with Aneurysmal Subarachnoid Hemorrhage. (10th July 2019) - Faulkner, Amanda L.; Bacon, James David; Fischer, Brian A.; Grupke, Stephen L.; Hatton, Kevin W.
Abstract : Extracorporeal membrane oxygenation (ECMO) is an important life-saving technology for patients with severe acute respiratory distress syndrome (ARDS). Unfortunately, ECMO has been traditionally contraindicated in patients with hemorrhagic neurologic diseases. The recent improvement in ECMO devices, increased utilization and experience with venovenous ECMO technologies among healthcare teams, and the use of ECMO without anticoagulation has expanded the potential populations that may benefit from ECMO. We present a case of successful utilization of venovenous ECMO for severe respiratory failure secondary to ARDS in a patient with aneurysmal subarachnoid hemorrhage and severe, episodic cerebral vasospasm. We also discuss important limitations and considerations for future successful use of ECMO in hemorrhagic stroke. This case report highlights the potential for this life-saving technology in patients with hemorrhagic stroke.